REFORMASI DAN MAKNA KEHIDUPAN SEKULER - Jadi Lima (STT Reformed Injili Internasional, 2014)
This article is a short historical survey of the emancipation of the meaning of non-ecclesiastical occupations and life ('secular life'), from the time of Eusebius to the sixteenth century Reformation. Here the theology of vocation proposed by Augustine of Hippo, Thomas Aquinas, Geert Grote of the Devotio Moderna, the Renaissance, Luther and Calvin, are being surveyed and analyzed, especially on their influences in the way people saw the 'secular life'. A special focus is given to the influence of Luther's and Calvin's theological views in elevating non-ecclesiastical life-spheres to be on the same level as respectable and as sacred as ecclesiastical life-spheres.?